Evaluation of the diagnostic value of oesophageal biopsies for direct immunofluorescence microscopy in mucous membrane pemphigoid: original report - Yilmaz, Osman K.; Dikmen, Onur; Beek, Nina van; Marquardt, Jens; Kirstein, Martha; Zillikens, Detlef; Schmidt, Enno (Acta dermato-venereologica, 2023)
Mucous membrane pemphigoid is an autoimmune blistering disorder characterized by predominant involvement of surface-close epithelia and linear depositions of immunoreactants at the dermal-epithelial junction on direct immunofluorescence microscopy. A major diagnostic difficulty is the frequent need for multiple biopsies to facilitate the diagnosis. Although oesophageal involvement is a rare, but life-threatening manifestation, the relevance of oesophageal direct immunofluorescence sampling is unclear. This retrospective monocentric study evaluated 67 non-lesional biopsies from 11 patients with mucous membrane pemphigoid and clinical symptoms suggestive of oesophageal involvement, comprising 31 samples from the oesophagus and 36 samples from other anatomical sites. Five patients (45.5%) exhibited endoscopic findings compatible with oesophageal involvement of mucous membrane pemphigoid. No correlation was identified between the presence of oesophageal lesions and direct immunofluorescence positivity in lesions from the oesophagus (p = 1.0). Oral and cutaneous samples were significantly more frequently positive by direct immunofluorescence than were oesophageal biopsies (p < 0.0001 and p = 0.0195, respectively). Oesophageal samples yielded significantly less IgG reactivity than oral and cutaneous lesions (p < 0.0001 and p = 0.0126, respectively), and less IgA antibody response than oral lesions (p = 0.0036). In conclusion, oesophageal direct immunofluorescence samples were inferior to oral and cutaneous biopsies for the diagnosis of mucous membrane pemphigoid even when oesophageal lesions compatible with mucous membrane pemphigoid were present at the time of biopsy.
Gesehen am 01.02.2024